PENGARUH METODE WORD SQUARE TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH ALIYAH MU’MIN MA’SHUM KOTA TASIKMALAYA - Isma Anggraeni; Abdul Muis Suja’i, Cecep (Program Studi Pendidikan Agama Islam, 2025)
This study aims to examine the effect of implementing the Word Square method on students’ learning outcomes in Akidah Akhlak at Madrasah Aliyah Mu’min Ma’shum Tasikmalaya. The research employed a quantitative approach with a sample of 28 students. The instruments used were learning outcome tests and questionnaires on the implementation of the Word Square method. Data analysis was conducted using validity and reliability tests, normality and linearity tests, as well as simple linear regression with the assistance of SPSS software. The results indicate that the Word Square method has a significant effect on students’ learning outcomes, with a significance value of 0.030 (< 0.05) and a regression coefficient of 0.796. The regression equation obtained is Y = 47.537 + 0.796X, indicating that each increase in the implementation of the Word Square method is followed by an improvement in students’ learning outcomes. In conclusion, this study confirms that the Word Square method is an effective teaching strategy, particularly in enhancing learning outcomes in Akidah Akhlak.